2020
DOI: 10.1186/s43055-020-00367-z
|View full text |Cite
|
Sign up to set email alerts
|

A solitary hypothalamic metastasis from prostatic cancer mimicking a giant thrombotic aneurysm and presenting with intraventricular hemorrhage and acute hydrocephalus: a case report

Abstract: Background Despite the high prevalence of prostate cancer, its brain parenchymal metastasis is not common and intracranial hemorrhage due to such a metastasis is even less common. This report presents a challenging case of solitary brain metastasis secondary to prostate cancer that gave rise to intraventricular hemorrhage and acute hydrocephalus mimicking a giant aneurysm. Case presentation A 77-year-old man with a history of prostate cancer, hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Fifty-seven [ 9 , 10 , 13 24 , 26 30 , 32 , 36 39 , 41 , 43 74 ] out of the 59 studies including 852 patients had reported BMs in PCa patients presenting with several clinical manifestations ranging from general symptoms such as hematuria, increased urinary frequency, and weakness to neurologic signs and symptoms such as aphasia, dysphasia, dysarthria, hemiplegia, headache, dizziness, confusion, double vision, visual field cut, ataxia, seizures, delirium, dementia, loss of appetite, and even behavioral changes. Moreover, different diagnostic methods including prostate-specific antigen (PSA), brain computed tomography (CT), brain magnetic resonance imaging (MRI), bone scan, multispectral immunofluorescence, immunohistochemistry (IHC), DNA sequencing, positron emission tomography (PET), prostate biopsy, and CSF analysis were used to diagnose BM in patients with PCa.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fifty-seven [ 9 , 10 , 13 24 , 26 30 , 32 , 36 39 , 41 , 43 74 ] out of the 59 studies including 852 patients had reported BMs in PCa patients presenting with several clinical manifestations ranging from general symptoms such as hematuria, increased urinary frequency, and weakness to neurologic signs and symptoms such as aphasia, dysphasia, dysarthria, hemiplegia, headache, dizziness, confusion, double vision, visual field cut, ataxia, seizures, delirium, dementia, loss of appetite, and even behavioral changes. Moreover, different diagnostic methods including prostate-specific antigen (PSA), brain computed tomography (CT), brain magnetic resonance imaging (MRI), bone scan, multispectral immunofluorescence, immunohistochemistry (IHC), DNA sequencing, positron emission tomography (PET), prostate biopsy, and CSF analysis were used to diagnose BM in patients with PCa.…”
Section: Resultsmentioning
confidence: 99%
“…As described in Table 2 , these include symptoms such as headache, nausea, vomiting, seizures, confusion, weakness, aphasia, visual disturbances, ataxia, motor dysfunction, mono/hemiparesis, mental status or behavioral changes, cranial nerve dysfunction, and delirium. It was also demonstrated that patients can be asymptomatic, and the diagnosis of BMs in PCa may be an incidental finding during other investigations [ 9 , 10 , 13 24 , 26 30 , 32 , 36 39 , 41 , 43 74 , 76 , 77 ].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations